Manajemen Risiko Pada Peternakan Kambing di Desa Dampyak Kabupaten Tegal - Aprilia Dwi Lestari; Amirah Amirah (Universitas 45 Surabaya, 2025)
The study aims to identify and analyze various types of risks faced by smallholder goat farmers in Dampyak Village, Tegal Regency, and to evaluate the risk management strategies they have implemented. A descriptive-analytical method was used with a survey approach involving five purposively selected goat farmers. Data was collected through interviews and questionnaires, then analyzed based on 23 risk indicators covering production, economic, environmental, and managerial aspects. The findings show that most indicators fall under the high-risk category, with an average aggregate score of 4,5. Major risks include extreme weather changes, livestock diseases such as scabies, limited forage availability, and market price fluctuations. From a managerial perspective, perspective, farmers still face challenges in record-keeping and adopting technology, although their awareness of risk management importance is relatively high. Mitigation strategies include routine vaccination, maintaining pen hygiene, providing alternative feed, and expanding marketing networks.